2005
DOI: 10.1074/jbc.m501890200
|View full text |Cite
|
Sign up to set email alerts
|

Y25S Variant of Paracoccus pantotrophus Cytochrome cd1 Provides Insight into Anion Binding by d1 Heme and a Rare Example of a Critical Difference between Solution and Crystal Structures

Abstract: Tyr25 is a ligand to the active site d 1 heme in as isolated, oxidized cytochrome cd 1 nitrite reductase from Paracoccus pantotrophus. This form of the enzyme requires reductive activation, a process that involves not only displacement of Tyr 25 from the d 1 heme but also switching of the ligands at the c heme from bis-histidinyl to His/Met. A Y25S variant retains this bis-histidinyl coordination in the crystal of the oxidized state that has sulfate bound to the d 1 heme iron. This Y25S form of the enzyme does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…Previous experiments performed on Y25S variant P. pantotrophus cytochrome cd 1 , which has His/Met ligands to both the oxidized and reduced c heme in solution, demonstrated that reduced pseudoazurin was able to reduce the protein (31). In contrast, we found that pseudoazurin failed to reduce M106H cytochrome cd 1 .…”
Section: Resultscontrasting
confidence: 81%
See 1 more Smart Citation
“…Previous experiments performed on Y25S variant P. pantotrophus cytochrome cd 1 , which has His/Met ligands to both the oxidized and reduced c heme in solution, demonstrated that reduced pseudoazurin was able to reduce the protein (31). In contrast, we found that pseudoazurin failed to reduce M106H cytochrome cd 1 .…”
Section: Resultscontrasting
confidence: 81%
“…It is well documented that the average midpoint redox potential of a His/Met coordinated c heme is commonly ∼200 mV in excess of a bishistidinyl coordinated c heme because methionine is more effective than histidine at stabilizing the reduced c heme iron (19,40). This is highlighted by the observation that, in this work, reduced pseudoazurin could not reduce the bishistidinyl M106H variant protein; however, it was able to reduce a Y25S variant with His/Met c heme coordination due to the higher midpoint potential of a His/Met c heme center (31).…”
Section: Discussionmentioning
confidence: 85%
“…2). Notably, no d 1 heme signals other than the trace of Fe(II)-NO were observed in the EPR spectrum of cd 1 -X reacted with oxidized pseudoazurin, fully consistent with the final product being the (EPR-silent (25,27)) all-ferric state of the enzyme with nitrite bound.…”
mentioning
confidence: 52%
“…To obtain the spectra of these complexes, fully reduced cytochrome cd 1 was mixed with nitrite in a stopped-flow apparatus, and spectra were recorded over a period of 2 s with a minimum data interval of 2 ms. cd 1 -X was either allowed to decay in the intense light of the diode array spectrophotometer (v) or was mixed with initially oxidized pseudoazurin (vi). Rows vii-ix refer to standard (model) cytochrome cd 1 complexes used in the assignment of spectra described in this work; vii and viii describe spectra of the Y25S variant of P. pantotrophus cytochrome cd 1 (27,34 cytochrome cd 1 ( Table 1). The final product of the reaction between pseudoazurin and cd 1 -X at pH 7.0 had a visible absorption peak at 641 nm, and when the same experiment was repeated at pH 6.0, the peak was at 639 nm.…”
Section: Table 1 Absorption Maxima For P Pantotrophus Cytochrome CD mentioning
confidence: 99%
See 1 more Smart Citation